(untitled) (Journal of the Bangladesh Agricultural University, 2024)
Effectiveness of endotrophic mycorrhizal fungus (Glomus mosseae) inoculation in eggplants was evaluated in pot experiments under net-house for management of wilt disease of brinjal caused by Fusarium oxysporum f. sp. melongenae. The ability of G. mosseae in mycorrhization of eggplant roots and spore abundance in soil were assayed in co-inoculated condition by F. oxysporum f. sp. melongenae and compared with untreated control plants. Significant variation in plant growth parameters viz. plant height, shoot length, root length, fresh weight and dry weight were recorded at 30, 60 and 90 Days After Transplanting (DAT). Glomus mosseae inoculated plants showed 58.90%, 39.00% and 41.97% higher plant height when co-inoculated with F. oxysporum f. sp. melongenae and G. mosseae compared to F. oxysporum f. sp. melongenae inoculated plants alone at 30, 60 and 90 DAT. Wilt incidence was reduced 74.47, 84.88, and 95.86% in co-inoculated plants compared to pathogen-inoculated plants at 30, 60 and 90 DAT. Wilt disease suppressing ability of G. mosseae is statistically comparable with positive control (Chemical fungicide- Carbendazim) from 50 DAT to 90 DAT. The sole application of G. mosseae resulted in significant increase in vegetative growth and mycorrhization of roots compared to untreated control. Mycorrhizal spore abundance in soil was significantly increased in sole application of G. mosseae than co-inoculation of F. oxysporum f. sp. melongenae and G. mosseae. Present findings have provided the evidence of ability of G. mosseae to enhance tolerance of eggplants against wilt pathogen and ensure an excellent symbiotic association with eggplant plants. J Bangladesh Agril Univ 18(3): 593–598, 2020 https://doi.org/10.5455/JBAU.113635